Functional and structural readouts for early detection of retinal involvement in multiple sclerosis - Al-Nosairy, Khaldoon O.; Duscha, Alexander; Buhr, Henrike; Lipp, Antonia; Desel, Christiane; Hegelmaier, Tobias; Thieme, Hagen; Haghikia, Aiden; Hoffmann, Michael B. (Frontiers in Integrative Neuroscience, 2023)
Introduction The retina, a window into the brain, allows for the investigation of many disease-associated inflammatory and neurodegenerative changes affecting the central nervous system (CNS). Multiple sclerosis (MS), an autoimmune disease targeting the CNS, typically impacts on the visual system including the retina. Hence, we aimed to establish innovative functional retinal measures of MS-related damage, e.g., spatially resolved non-invasive retinal electrophysiology, backed by established morphological retinal imaging markers, i.e., optical coherence tomography (OCT). Methods 20 healthy controls (HC) and 37 people with MS [17 without history of optic neuritis (NON) and 20 with (HON) history of optic neuritis] were included. In this work, we differentially assessed photoreceptor/bipolar cells (distal retina) and retinal ganglion cell (RGC, proximal retina) function besides structural assessment (OCT). We compared two multifocal electroretinography-based approaches, i.e., the multifocal pattern electroretinogram (mfPERG) and the multifocal electroretinogram to record photopic negative response (mfERGPhNR). Structural assessment utilized peripapillary retinal nerve fiber layer thickness (pRNFL) and macular scans to calculate outer nuclear thickness (ONL) and macular ganglion cell inner plexiform layer thickness (GCIPL). One eye was randomly selected per subject. Results In NON, photoreceptor/bipolar cell layer had dysfunctional responses evidenced by reduced mfERGPhNR-N1 peak time of the summed response, but preserved structural integrity. Further, both NON and HON demonstrated abnormal RGC responses as evidenced by the photopic negative response of mfERGPhNR (mfPhNR) and mfPERG indices (P < 0.05). Structurally, only HON had thinned retina at the level of RGCs in the macula (GCIPL, P < 0.01) and the peripapillary area (pRNFL, P < 0.01). All three modalities showed good performance to differentiate MS-related damage from HC, 71–81% area under curve. Conclusion In conclusion, while structural damage was evident mainly for HON, functional measures were the only retinal read-outs of MS-related retinal damage that were independent of optic neuritis, observed for NON. These results indicate retinal MS-related inflammatory processes in the retina prior to optic neuritis. They highlight the importance of retinal electrophysiology in MS diagnostics and its potential as a sensitive biomarker for follow-up in innovative interventions.